Readiness of Financial Advisors to Adopt Fintech on Customer Experience - Arciaga, Charles Joaquin (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between financial advisors’ readiness to adopt fintech-modeled services and customer experience in the Philippine life insurance industry. Anchored on the Technology Acceptance Model, Unified Theory of Acceptance and Use of Technology, and SERVQUAL, the study focused on technological literacy and organizational support as indicators of advisor readiness, while customer experience was measured through service responsiveness, service accessibility, communication quality, and trust and satisfaction. Perceived usefulness, perceived risk, and customer age were examined as moderating variables. A quantitative correlational research design was used, with data gathered through a structured self-administered questionnaire distributed via Google Forms. The respondents were 160 existing life insurance policyholders from Muntinlupa, Parañaque, and Las Piñas who had experience with fintech-enabled insurance services. Descriptive statistics, Pearson correlation, multiple linear regression, and moderated multiple regression were used to analyze the data. Findings showed that financial advisors’ readiness was generally high and had a significant positive relationship with customer experience. Advisor readiness significantly predicted customer experience, explaining 61.7% of its variance. Customer experience was high in communication quality, trust and satisfaction, and service accessibility, while service responsiveness was only moderate. Perceived usefulness significantly strengthened the relationship between advisor readiness and customer experience, while perceived risk did not significantly moderate the relationship. Customer age also moderated the relationship, showing that fintech-enabled service experiences vary across age groups. The study concluded that effective fintech adoption in life insurance depends on both technological capability and human-centered advisory support. It aligns with SDG 8, SDG 9, and SDG 17 by supporting professional readiness, digital innovation, and stakeholder collaboration. The study contributes to technological, institutional, and socio-economic sustainability by promoting more responsive, accessible, and customer-centered digital insurance services.